Prohibition of novitiae mass Canons 34; 652 and 586 - Jaramillo, Eileen J. (2006)
"Can a diocesan bishop forbid celebration of Sunday Mass in the novitiate and compel all novices of different religious institutes in his diocese to attend Sunday Mass only in their parish churches?"
Keywords: Katholische Kirche; Katholische Kirche; Katholische Kirche; Verbot; Liturgisches Recht